Incidence of Salmonella and Escherichia coli in fish farms and markets in Dinajpur, Bangladesh - Ava, A; Faridullah, M; Lithi, UJ; Roy, VC (Bangladesh Journal of Scientific and Industrial Research, 2020)
The research work was conducted to assess the incidence of Salmonella and Escherichia coli (E. coli) contamination in different fish farms and fish markets of Dinajpur district of Bangladesh. The level of incidence of Salmonella contamination was greater in scum samples (93.8%) and for E. coli the higher contamination found in water samples (81.3%). The study showed that, water and fish samples were also Salmonella positive and the percentage was 87.5% and 57.8% respectively and for E. coli contamination about 75% of scum and 75.6% of fish samples were E. coli positive among fish farms samples. In case of market, both basket and fish sample were tested Salmonella positive, the level of incidence of Salmonella contamination was higher for basket samples (100%) and lower in fish samples (48.9%). Meanwhile, E. coli contamination for fish, basket, and mat samples were 75.6%, 68.8% and 75% respectively. Therefore, the results are very much alarming. Bangladesh J. Sci. Ind. Res.55(1), 65-72, 2020